Analisis Motivasi Karyawan PT. Kimia Farma Tbk Plant Watudakon Jombang - Syahrir; Amrullah, Ahmad Musyrifin; Rani, Rani (CV Warnak Johanna Nusantara, 2024)
ABSTRACT Abstracts - Employees are an important asset of a company to achieve the goals of the company's vision and mission. To retain employees, leaders are needed who are able to motivate their employees. Motivation is a good desire in a person to do something both consciously and unconsciously, done with enthusiasm so that the goal can be achieved. With strong motivation, a company can develop rapidly and vice versa, if there is no motivation for its employees, the company will not develop or advance. The success of a company really depends on how the activity and creativity of the human resources in the company. Therefore, researchers conducted research at the company PT Kimia Farma Tbk Plant Watudakon in Jombang with data collection methodology, namely observation, documentation and questionnaires and discussed what factors affect employee motivation with data qualitative data analysis methods with the data used is quantitative data. This study uses a closed interview technique by circulating several statements that are typed online via google form. From the research results, the results for physiological needs are 78.6% and 65.7%, the need for security is 81.5% and 70%, social needs are 91.4% and 64.3%, self-esteem or ego needs are 70% and 77.1%, and self-actualization needs are 81.5% and 32.8%. From the existing conclusions, it is found that the need for self-actualization is the lowest dimension of motivation. This indicates that many employees can do work outside of their job desk, so the author suggests that companies further explore employee abilities through job enlargemenet, job enrichment, job rotation and job empowerment programs.